Seroprevalence of Antibodies to Severe Acute Respiratory Syndrome Coronavirus 2 Among Healthcare Workers in Kenya. (23rd April 2021) - Etyang, Anthony O; Lucinde, Ruth; Karanja, Henry; Kalu, Catherine; Mugo, Daisy; Nyagwange, James; Gitonga, John; Tuju, James; Wanjiku, Perpetual; Karani, Angela; Mutua, Shadrack; Maroko, Hosea; et al.
Abstract: Background: Few studies have assessed the seroprevalence of antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among healthcare workers (HCWs) in Africa. We report findings from a survey among HCWs in 3 counties in Kenya. Methods: We recruited 684 HCWs from Kilifi (rural), Busia (rural), and Nairobi (urban) counties. The serosurvey was conducted between 30 July and 4 December 2020. We tested for immunoglobulin G antibodies to SARS-CoV-2 spike protein, using enzyme-linked immunosorbent assay. Assay sensitivity and specificity were 92.7 (95% CI, 87.9-96.1) and 99.0% (95% CI, 98.1-99.5), respectively. We adjusted prevalence estimates, using bayesian modeling to account for assay performance. Results: The crude overall seroprevalence was 19.7% (135 of 684). After adjustment for assay performance, seroprevalence was 20.8% (95% credible interval, 17.5%–24.4%). Seroprevalence varied significantly ( P < .001) by site: 43.8% (95% credible interval, 35.8%–52.2%) in Nairobi, 12.6% (8.8%–17.1%) in Busia and 11.5% (7.2%–17.6%) in Kilifi. In a multivariable model controlling for age, sex, and site, professional cadre was not associated with differences in seroprevalence. Conclusion: These initial data demonstrate a high seroprevalence of antibodies to SARS-CoV-2 among HCWs in Kenya. There was significant variation in seroprevalence by region, but not by cadre. Abstract : In this study of antibodies to severe acute respiratory syndrome coronavirus 2 among healthcare workers in 3 counties in Kenya, we found significant regional differences in seroprevalence but no differences according to professional cadre.